Gulf of Mexico Origin, Waters, and Biota : Volume 4, Ecosystem-Based Management - Yáñez-Arancibia, Alejandro; Day, John W., 1945- (Harte Research Institute for Gulf of Mexico Studies series., 2013)
The fourth volume in the Harte Research Institute's landmark scientific series on the Gulf of Mexico provides a comprehensive study of ecosystem-based management, analyzing key coastal ecosystems in eleven Gulf Coast states from Florida to Quintana Roo and presenting case studies in which this integrated approach was tested in both the US and in Mexico. Two overview chapters cover related information on Cuba and on coastal zone management in Mexico. The comprehensive data on management policies and practices in this volume give researchers, policy makers, and other concerned parties the most up-to-date information available, supporting and informing initiatives to sustain healthy ecosystems so that they can, in turn, sustain human social and economic systems in this important transnational region. Combined with the second volume in this series, which examines the coastal and ocean-based economy of the Gulf region, Ecosystem-Based Management provides pivotal empirical information on how human activity can be managed in an environmentally sustainable way. This important research points the way to better stewardship of the Gulf's valuable natural resources, ensuring their availability for future generations.